The Development of Information and Telecommunication Infrastructure of Rostov-on-Don as Part of Preparation for the FIFA World Cup 2018 ("Journal "U". Economy. Management. Finance.", 2017)
This article covers the issues of neсessity of the development of information and telecommunication infrastructure in the daily lives of citizens, in a business environment and at the state level. Particularly, this topic becomes more important in connection with holding of FIFA World Cup 2018. The need for modernization of this industry in Russia is shown by the example of one of the host cities of the World Cup. The study aims to answer the questions: what level of the development of info-telecommunications infrastructure is today and how it may affect the marketability of the regions and the state as a whole.
Keywords: information and telecommunication infrastructure; LTE; GPON